Bale Banjar as a Space for Deliberation and the Preservation of Balinese Culture in Kuta - Mitha Mahastuti; Nyoman Ratih Prajnyani Salain; Ni Made Adriana Murliana Bimar Zakharia (Architectural Research Journal, 2025)
This study examines the transformation of the functions and architectural form of the Bale Banjar in Kuta as a space for communal deliberation and the preservation of Balinese culture amid modernization, globalization, and the pressures of tourism. Employing a qualitative phenomenological approach within an interpretive paradigm, the research involved participant observation during pesangkepan wargi (customary deliberation meetings), in-depth interviews with 5–8 informants (including kelian banjar and senior krama), and triangulation with historical archival sources, focusing on three Bale Banjar in the Kuta area. The findings reveal hybrid adaptations of the bale pesangkepan to accommodate economic discussions (accounting for 60% of sessions), an increase in the frequency of deliberations to once every two weeks, the persistence of nonverbal interactions and the bale kulkul as a traditional calling symbol, and the addition of modern LPG-based perantenan (kitchens), which extend the duration of krama participation by 30–40% per session through the provision of fast food. The discussion affirms the resilience of the Bale Banjar through the principles of Tri Hita Karana and Nawa Sanga zoning, wherein material adaptations enhance pawongan (human relations) without eroding the spiritual awig-awig, although the growing dominance of material concerns risks shifting customary priorities. The conclusion highlights the Bale Banjar as a hybrid living entity of the Desa Pakraman, and recommends architectural conservation as well as longitudinal mixed-methods studies for national architectural design guidelines. The study contributes a narrative model of deliberative space for the preservation of urban Balinese culture.